Feed budget: a management tool for livestock production systems - Vargas Martínez, Juan (2022)
Forage management, strategic supplementation and the incorporation of monitoring tools for making timely decisions allow the development of livestock production systems. In this way, a feed budget is a tool that allows making a balance of the dry matter of the farm in a defined period of time, by comparing different units of measurement and making decisions regarding the management of forages and the purchase of feed resources as feeding strategies. In addition, elements such as the dry matter requirements of the groups of animals on the farm and the supply of dry forage throughout the year and its production cost must be considered. When comparing results from the exemplification of contrasting productive scenarios, it was found that, by having an unrestricted forage supply, feed costs increase by 208% due to the application of fertilization, the sowing of forage crops and the purchase of feeds from outside the farm. In another scenario, when there is evidence of a decrease in the forage supply, the scenario in which forage crops are used is the one with the lowest feed cost (COP$201/kg DM). In conclusion, the feed budget allows creating of feed scenarios that support the producer's decision-making, reduce feed costs and meet production goals.